2018
DOI: 10.5812/ircmj.62517
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Honey and Spirulina Platensis on Acetic Acid-Induced Ulcerative Colitis in Rats

Abstract: Background: Overproduction of reactive oxygen species (ROS) causes increased lipid peroxidation, decreased intestinal epithelial barrier integrity, and ultimately mucosal disruption and ulceration. Several studies have confirmed the antioxidant, antiinflammatory, and immunomodulatory properties of Spirulina Platensis (SP), edible blue -green algae, in various inflammatory diseases. In addition, natural honey, a source of phenolic and flavonoid compounds, is a powerful antioxidant, which can help prevent chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
3
4
0
Order By: Relevance
“…These results are consistent with a previous study [ 33 ], which revealed that 100 mg canagliflozin every other day improved endothelial function in diabetic patients with suspected coronary disease through decreased markers of inflammation. Furthermore, the present study reported that AA inducing marked oxidative stress with significantly elevated MDA and reduced TAC in colonic tissue, which is in harmony with a previous study [ 34 ]. In another study, intrarectal administration of 3% v / v AA increased colonic MDA and decreased colonic TAC due to increased production of oxidant radicals and generation of excessive ROS, which induced damage of biologic molecules of cellular components [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with a previous study [ 33 ], which revealed that 100 mg canagliflozin every other day improved endothelial function in diabetic patients with suspected coronary disease through decreased markers of inflammation. Furthermore, the present study reported that AA inducing marked oxidative stress with significantly elevated MDA and reduced TAC in colonic tissue, which is in harmony with a previous study [ 34 ]. In another study, intrarectal administration of 3% v / v AA increased colonic MDA and decreased colonic TAC due to increased production of oxidant radicals and generation of excessive ROS, which induced damage of biologic molecules of cellular components [ 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Cphycocyanins and β-carotene contained in Spirulina can block NF-κB activity and thus suppresses TNF-α [38]. Moreover, β-carotene also inhibits the expression of proinflammatory cytokines such as IL-1β and IL-6 in stimulated macrophages by suppressing their transcription [39].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary Spirulina supplementation significantly decreased the level of MDA values and increased activity of SOD and GPX in both non challenged treated groups (G2 and G3) and in challenged treated groups (G5 and G6) as compared to the control negative group (G1) and control positive group (G4) respectively (Table 7). There was a significant increase (p < 0.05) in the level of SOD and GPX G. Abd El-Dayem et al 2021/ Effect of Spirulina platensis in quail Mans Vet Med J 22:2 (2021) [38][39][40][41][42][43][44][45][46][47] with an increased dietary level of spirulina inclusion from (1-2 g).…”
Section: Serum Antioxidant Statusmentioning
confidence: 99%
“…Rezaei et al reported that feeding rats with honey (which contains phenols and flavonoids) and Spirulina Platensis (containing antioxidants) may protect against UC development induced by acetic acid. The supplementation of polyphenols influences, for instance, the downregulation of various inflammatory pathways [ 130 ].…”
Section: Polyphenolsmentioning
confidence: 99%